2010
DOI: 10.1007/s00592-010-0225-1
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids inhibit insulin-mediated glucose transport associated with actin remodeling in rat L6 muscle cells

Abstract: In skeletal muscle cells, insulin stimulates cytoskeleton actin remodeling to facilitate the translocation of glucose transporter GLUT4 to plasma membrane. Defect of insulin-induced GLUT4 translocation and actin remodeling may cause insulin resistance. Free fatty acids cause insulin resistance in skeletal muscle. The aim of this study was to investigate the effects of fatty acids on glucose transport and actin remodeling. Differentiated L6 muscle cells expressing c-myc epitope-tagged GLUT4 were treated with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Free fatty acids are considered as a new marker of IR [17]. The investigations of the last years were shown that fatty acids inhibit insulin-stimulated glucose transport in muscle cells [18]. It is also established, that chronic increasing of free fatty acids in serum leads to IR development [15] and that fatty acids induce IR of man skeletal muscles due to the defects of insulin-dependent glucose transportation [18].…”
Section: Calcitonin and Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Free fatty acids are considered as a new marker of IR [17]. The investigations of the last years were shown that fatty acids inhibit insulin-stimulated glucose transport in muscle cells [18]. It is also established, that chronic increasing of free fatty acids in serum leads to IR development [15] and that fatty acids induce IR of man skeletal muscles due to the defects of insulin-dependent glucose transportation [18].…”
Section: Calcitonin and Insulin Resistancementioning
confidence: 99%
“…The investigations of the last years were shown that fatty acids inhibit insulin-stimulated glucose transport in muscle cells [18]. It is also established, that chronic increasing of free fatty acids in serum leads to IR development [15] and that fatty acids induce IR of man skeletal muscles due to the defects of insulin-dependent glucose transportation [18]. Enhanced free fatty acids level reveals the direct metotoxical effect on the secretory function of pancreas β-cells and decreases insulin-dependent glucose utilization by muscle cells, resulting peripheral IR develops.…”
Section: Calcitonin and Insulin Resistancementioning
confidence: 99%
“…Skeletal muscle glucose uptake and metabolism play a key role in the regulation of whole-body glucose homeostasis in normal and diabetic subjects (10,11). Glucose uptake is the rate-limiting step of glucose utilization and is depressed in cases of insulin resistance, a process characterized by the reduced availability of sarcolemmal glucose transporter 4 (GLUT4) translocation and consequential lower glucose uptake (12,13).…”
Section: Introductionmentioning
confidence: 99%